Is there a role for nutritional advice during breastfeeding for infant colic relief? A mixed-method study - Belén Vázquez; Michelle Barrow; James Neil; Karin Seidler (Heliyon)
Objective: This study aimed to explore the extent and impact of maternal dietary change for colic relief in a cohort of breastfeeding women. Method: A mixed-method non-sequential approach was devised, including a web-based survey (n = 66) and three semi-structured interviews. Results: Most women (70 %) changed their diet while breastfeeding a baby with colic and perceived a positive impact on their babies (63 %). The choice of foods eliminated was individual, based on a process of trial and error and on the perceived benefit to the baby. A sub-group of colicky babies, those with less intense colic symptoms, benefited significantly from the removal of cruciferous vegetables (p = 0.01) and were found to be ‘less windy’ (p = 0.10, ES0,20), a result trending towards statistical significance. Women felt unsupported while making changes to their diet. When dietary change brought relief to the baby, it turned into a coping tool for women facilitating extended breastfeeding. Conclusions: Maternal dietary change can play a positive role in providing relief to breastfed babies with colic. Novel findings from this study revealed that different baby subtypes got relief from the elimination of different foods. This underscores the potential of personalised nutritional advice for colic relief in breastfed babies.